CULTURAL CONSIDERATIONS IN TASK-BASED INSTRUCTION FOR EFL STUDENTS - Maftuna Abdurasulova , (TADQIQOTLAR.UZ, 2024)
Task-Based Instruction (TBI) is widely recognized for its effectiveness in promoting communicative competence among English as a Foreign Language (EFL) students. However, the cultural backgrounds of learners play a significant role in the implementation and effectiveness of TBI. This article explores the impact of cultural considerations on TBI, analyzing how cultural factors influence task design, student engagement, and learning outcomes. By reviewing relevant literature and presenting empirical findings, this study aims to provide insights into how cultural awareness can enhance the effectiveness of TBI in diverse EFL contexts.